Community-Based Implementation of the Elderly Posyandu Program in Sidodadi Village: Pelaksanaan Program Posyandu Lansia Berbasis Masyarakat di Desa Sidodadi - Parwestri, Diana; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2025)
General Background: The aging population in Indonesia necessitates integrated community health initiatives to maintain elderly well-being. Specific Background: Sidodadi Village in Sidoarjo Regency implemented the Elderly Posyandu Program to improve elderly health status through preventive and promotive services. Knowledge Gap: However, studies focusing on its operational dynamics at the village level are still limited. Aims: This study aims to describe and analyze the implementation of the Elderly Posyandu Program and identify supporting and inhibiting factors. Results: The findings show that the program is relatively effective due to active community participation and committed health cadres, yet constrained by limited medical personnel and facilities. Novelty: The integration of Edward III’s policy implementation theory provides a systematic understanding of how communication, resources, disposition, and bureaucratic structure affect program performance. Implications: Strengthening cadre training, optimizing health infrastructure, and enhancing coordination among stakeholders are essential for program sustainability. Highlights: Cadre participation supports program success. Limited facilities reduce elderly service quality. Coordination and training need improvement.